Pengaruh Fasilitas Belajar dan Lingkungan Belajar Terhadap Prestasi Belajar Pada Siswa Kelas Atas SD Negeri 3 Ngraji Tahun Ajaran 2015/2016 - Isnawati, Zuli; , Dra. Risminawati, M.Pd (2016)
Education is a bridge towards a more useful life. To get a success certainly needs to be a process and that process be named learning. The purpose of this research was to determine include: 1) The effect of learning facilities to learning achievement at class student the top SD Negeri 3 Ngraji Academic Year 2015/2016, 2) The effect of the learning environment to learning achievement at class student the top SD Negeri 3 Ngraji Academic Year 2015/2016, 3) The effect of learning facilities and learning environment to learning achievement at class student the top SD Negeri 3 Ngraji Academic Year 2015/2016. This type of research quantitative approach to the method of research Ex-Post Facto. The analysis technique used is multiple linear regression, t test, and test f. Based on the analysis of data: 1) the equation regression coefficient obtained Y= 33,395+ 0,331X1 + 0,155X2. 2) The t test results learning facilities tcount (2,062) > ttable (2,048) finished 2,062 > 2,048, so it learning facilities a positive effect on student achievement. 3) learning environment with positive effect on student achievement, it is based on t test results tcount (2,860) > ttable (2,048) finished 2,860 > 2,048, so it learning environment a positive effect on student achievement. 4) The test results f fcount value (7,678) > Ftable (3,35) finished 7,678 > 3,35 or significant value 0,001 < 0,05, mean learning facilities and learning environment together positive effect on learning achievement at class student the top SD Negeri 3 Ngraji Academic Year 2015/2016. Based on the calculation of the relative contribution and effective contribution shows that the variable learning facilities give the relative contribution of 36,70% and the effective contribution of 13,32% to the learning achievement at class student the top, variable learning environment relative contributed of 63,30% and contributions effective amounted to 22,98% to the learning achievement at class student the top. While the coefficient of determination (R2) was obtained for 0,363, so the learning facilities and learning environment contributed 36.3% to the learning achievement at class student the top SD Negeri 3 Ngraji Academic Year 2015/2016. Keywords: Learning Facilities, Environmental Learning, Learning Achievement